PV Systems based High Gain Converter using CI and SCC Techniques - S. Sankarananth; P. Sivaraman (Indonesian Journal of Electrical Engineering and Informatics (IJEEI), 2022)
In this paper, new techniques of a CI and SCC-based step-up higher-level voltage DC_DC converter were implemented. The CI and SC charging and discharging the energy respectively to attain higher gain. The stress in switching volt level and inductance leakage is detached using the clamp circuitry. The reversed retrieval problem in the diode was eradicated with the help of Coupled Inductor (CI). The new topology to get more gain of the voltage and improved efficiency. The steady state analysis with the operation procedures of novel DC_DC converter is discussed here. In proposed model, input voltage is 24V & Vo is 410V, Pmax is 150W was given to get ηmaximum of 96.4%.